Factors Affecting Bank Stability in Indonesia - Sita Aisha Gemala; Susy Muchtar (Jurnal Economic Resource, 2026)
This research aims to analyze the factors affecting bank stability in Indonesia. The data used in this research is secondary data on the banking sector sourced from the financial reports of companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The research sample was selected using the purposive sampling method, resulting in 35 companies that are suitable for the research. The data analysis used for hypothesis testing is panel data regression analysis using the Eviews 9 program. The results of the study show that bank size and the economic cycle affect bank stability. This indicates that the larger the bank size, the more stable the bank can be in obtaining income. For the economic cycle variable, if GDP growth contributes to bank stability, it indicates management’s ability to manage risk effectively. Strict supervision and effective risk management are key to the stability of the banking system. Various factors, both internal and external, such as risk management and business strategy, significantly influence bank stability. And external (like economic cycles and government policies). By effectively managing assets and adapting to economic conditions, banks can enhance their stability and contribute to the overall stability of the financial system.